1963
DOI: 10.1139/v63-151
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Chromyl Chloride With Some Olefins: Part I. The Products From Cyclohexene, Cyclopentene, 1-Hexene, and 2-Methyl-1-Pentene

Abstract: Chromyl chloride in carbon tetrachloride solution reacts in the cold with cyclohexene, cyclopentene, and 1-hexene to give the various isomeric chlorohydrins as the major products. The major product from 2-methyl-1-pentene was 2-methylpentanal. Significant amounts of α-chloro carbonyl compounds and some α,β-unsaturated carbonyl compounds were also produced. The significance of these results is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1969
1969
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…It could be excluded that they were generated in the matrix by isomerization of epoxide complexes and on permethylation of the olefinic bond (i.e., employment of TME) their formation route was completely suppressed. Moreover, first representatives for OCrCl 2 ···epoxide complexes, often proposed as intermediates in the literature, ,,, have been isolated and characterized. Both types of complexes should be considered as respectable intermediates also under thermal conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be excluded that they were generated in the matrix by isomerization of epoxide complexes and on permethylation of the olefinic bond (i.e., employment of TME) their formation route was completely suppressed. Moreover, first representatives for OCrCl 2 ···epoxide complexes, often proposed as intermediates in the literature, ,,, have been isolated and characterized. Both types of complexes should be considered as respectable intermediates also under thermal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For quite some time the olefin oxidation with chromyl chloride (CrO 2 Cl 2 ) seemed to proceed completely unspecifically, and reports with the most different product palettes accumulated. The first selective oxidation was reported in 1969 by F. Freeman et al claiming that reductive workup of the reaction mixtures in the presence of zinc enables the isolation of carbonyl compounds in good yields . However, mainly disubstituted, electron-rich olefins had been employed in this investigation. In 1973 K. B. Sharpless et al found that chloroketones are formed selectively if the reactions are carried out in acetone at −78 °C, and they related the findings made on reductive workup 7-11 to the reduction of these oxychlorides by zinc.…”
Section: Introductionmentioning
confidence: 93%
“…Transition metal oxides and halides are applied extensively as oxidants in processes where oxygen or halogen is inserted into a C−H linkage or added to an olefin double bond. Oxidation carried out in this way is often relatively gentle and remarkably specific compared to the direct application of elemental oxygen or halogen. Many of the oxidation processes have been subject to mechanistic studies. …”
Section: Introductionmentioning
confidence: 99%
“…The nature of these products speaks strongly against the proposals of Stairs et a/. (10) and Nenitzescu and coworkers (1 1) both of whom proposed that the a$-unsaturated carbonyl compounds formed in chromyl chloride oxidations of olefins could arise from the elimination of HCl from an a-chloroketone. This rather unlikely process would yield a$-unsaturated derivatives of pinocamphone (2) but none of these products are found.…”
Section: Traduit Par Le Journal]mentioning
confidence: 91%